Analysis of wet and dry encounters in the Yangtze River Basin based on the Copula function family and research on the probability of floods and droughts occurrence - Jinhang Li; Mengdie Zhao; Yuping Han (PLoS ONE, 2025)
As the largest river in China, exploring the evolution characteristics of rainfall in the upper, middle, and lower reaches of the Yangtze River and analyzing the frequency of wet and dry encounters play a significant role in flood and drought prevention in the Yangtze River Basin. This study employs the Mann-Kendall test, 5-year moving curve, Pettitt test method, and Morlet wavelet analysis method to analyze and diagnose the trend, abrupt changes, and periodicity of rainfall in the Yangtze River Basin. By fitting the optimal rainfall marginal distribution and Copula joint distribution model, the probability of wet and dry period encounters and their changing patterns in the upper, middle, and lower reaches of the Yangtze River are calculated and analyzed. Based on the results of wet and dry encounters, a Bayesian network model for flood and drought management is constructed and simulated. The study shows that: (1) There is no significant change in the overall rainfall pattern in the Yangtze River Basin, with periodic changes of 14, 33, and 10 years in the upper, middle, and lower reaches respectively, and abrupt change years in 1997, 1986, and 1979. (2) Apart from the middle and lower reaches of the Yangtze River, where the number of encounters between wet and dry years reaches up to 15 times, the frequency of asynchronous and synchronous wet and dry periods is generally evenly distributed across the upper, middle, and lower reaches. (3) Based on Bayesian prior inference and simulation results, the probabilities of simultaneous floods and droughts occurring in the upper, middle, and lower reaches are 53% and 47%, respectively. When the upper, middle, and lower reaches are all in wet or dry years, the probability of floods and droughts in the Yangtze River Basin is 91%. The research results provide a theoretical basis for scientifically grasping the changes in water conditions in the Yangtze River Basin and for flood and drought prevention.